Development of MITEDA (Mitigation of Earthquake Damage) Media for Wave Physics Using a STEM Approach to Enhance Students’ Computational Thinking Skills - Kristian Dinata; Afrizal Mayub; Iwan Setiawan; Henny Johan; Sutarno Sutarno (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study is to develop and evaluate the effectiveness of a learning media called MITEDA (Mitigation of Earthquake Damage), which is based on the STEM approach and computational thinking, to support the teaching of wave physics. The study focuses on both the development process of the media and its impact on improving students’ computational thinking skills through contextual problem-solving using earthquake simulation and sensor-based data. Methodology: The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Tools used include Arduino Uno, SW-420 vibration sensor, LCD 16x2, and a buzzer. Software includes Arduino IDE and Proteus. Data collection used expert validation sheets, student questionnaires, observations, and computational thinking tests. Main Findings: The MITEDA learning media, comprising a digital seismograph kit and instructional module, was rated “highly feasible” by experts (Aiken’s V ≥ 0.80) and received positive student feedback for usability and engagement. Statistical analysis showed a significant improvement in computational thinking skills for the experimental group (N-Gain = 0.84) compared to the control group (N-Gain = 0.56), t(69) = 8.875, p < 0.001, d = 2.716, with the highest gains in abstraction and consistent high-level algorithmic performance. Novelty/Originality of this study: This study presents an innovative learning media, MITEDA, integrating STEM and computational thinking through earthquake simulation using Arduino-based sensors. It advances wave physics learning by providing real-time vibration data and contextual problem-solving, enhancing students’ analytical skills.